A Study of Fluid Convective Flow in a Room: A Research-Based Learning on Heat Transfer Topics - Budi, Gunarjo Suryanto; Hartanto, Theo Jhoni; Farcis, Fenno; Putri, Umi Amanda; Siloam, Kristanoval (FKIP Universitas Lampung, 2024)
Abstract: This study is motivated by the importance of developing learning patterns that emphasize the formation and understanding of students through active learning. One form of learning that can support this goal is research-based learning. Research-based learning promotes student-centeredness and integrates research into a meaningful learning process. In this work, the students are actively involved in real research related to fluid convective flow topics. This research aims to describe the impact of research-based learning on students' understanding of convective fluid flow topics. A pre-experimental research method with a one-group pre-test and post-test design was used. Participants were taken from students in the Physics Education Study Program at the University of Palangka Raya taking thermodynamics courses. The number of participants was 20 students. The test instrument is in the form of essay questions consisting of five questions related to fluid convective flow material. The finding indicates that prospective teacher students' understanding was significantly increased with a high category (N-Gain score of 0.74). Based on this study, research-based learning activities could be considered an alternative to conducting meaningful learning activities, especially in fluid convective flow topics. Keywords: fluid flow, physics learning, research-based learning.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp53-65